High-performance cycloid inspired wearable electromagnetic energy harvester for scavenging human motion energy. (15th December 2019) - Maharjan, Pukar; Bhatta, Trilochan; Salauddin Rasel, M.; Salauddin, Md.; Toyabur Rahman, M.; Park, Jae Yeong
Highlights: A wearable energy harvester based on cycloid structure is proposed. The high output performance of cycloid based energy harvester is demonstrated. A cycloid curve is the path with quickest descent for an object to travel. The cycloid curve increases the speed of magnetic ball and increase induced emf. 5 s of wrist motion successfully powered a sports stopwatch for more than 16 min. Abstract: Eco-friendly and wearable power sources are in high demand because of the hasty growth in smart wearable electronic devices including health care monitoring sensors. Here, we successfully designed and fabricated a high-performance cycloid-inspired wearable electromagnetic energy harvester (CEEH) for scavenging low frequency (≤5 Hz) human motion energy. The proposed CEEH introduces a cycloid curved structure as an energy harvester for the first time which provides the fastest descent for the freely rolling spherical magnet in the curve path, resulting an increment in the rate of cutting magnetic flux. In order to demonstrate the capability of the proposed device for harvesting electrical energy from the natural human motions such as arm swinging and vibration, hand-shaking vibration motion tests and custom-made swinging arm tests were performed. The as-fabricated harvester can deliver an average power of 8.8 mW under the excitation vibration of 5 Hz at an optimum load resistance of 104.7 Ω. Moreover, it can continuously power a commercial sporty stopwatch for more than 16 min and a wristwatch for more than 34 min from just 5 s of hand motion vibration. The proposed device exhibits much enhanced performance which is more than 1.45 times higher in comparison with other different geometric structures such as straight and circular design. The outstanding energy harvesting capability of the proposed energy harvester shows huge potential as a wearable energy harvester for wrist and foot worn applications and as a sustainable power source for powering smart wearable or portable electronic devices and systems.